Analysis of the Role of Basic Sector Economic Growth on Poverty in Aceh Province Special Region for Implementing Islamic Sharia - Farma Andiansyah; Rila Maufira; Saddam Hasrul (El-Qish: Journal of Islamic Economics, 2024)
Economic growth is expected to impact income inequality reduction and poverty alleviation. The diversity of economic sectors raises fundamental questions about which sectors can effectively reduce poverty through potential sectors. The economy of Aceh has experienced significant growth, particularly in key or leading sectors, yet the population of Aceh remains trapped in poverty. This study aims to analyze the impact of key sectors on poverty in the Province of Aceh. This research employs a quantitative method using a panel data analysis model without selecting the best model. The results of this study indicate that, simultaneously, key sectors have a significant negative impact on poverty in Aceh. However, on a partial basis, only the trade, transportation, government, and health sectors have a significant negative correlation with poverty in Aceh. Conversely, the agriculture, trade, and real estate sectors do not affect poverty in Aceh.